Pengaruh Panhisterektomi dan Konsumsi Suplemen 1,25-Dihidroksivitamin D3 Selama 1,5 Bulan terhadap Retensi Kalsium pada Tikus Wistar - Hartiningsih -; Devita Anggraini; Irkham Widiyono (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2010)
The objective of the research was to study the effect of panhisterectomy and 1,25-dihydroxyvitamin D3supplement consumption for 1.5 months on Ca retention of Wistar rats fed with casein. Twenty female ofWistar rats, 8 weeks of age were randomly divided into four groups (normal group N and NK,panhisterectomized group H and HK) in wich group consisted of 5 rats. Group N and H rats were fed witha standard diet, while group NK and HK rats were fed with a standard diet+1,25-dihydroxyvitamin D3supplement. At 19 weeks of age, they were placed into individual metabolic cages for balance studies.From day 7 to 11 of the balance studies, daily unconsumed food, urine, and feces were collected andrecorded for Ca analyses. The research results showed that Ca comsumption and fecal Ca excretion weresignificantly higher (P<0.05) in panhisterectomized rats consuming 1,25-dihydroxyvitamin D3 supplement,as compared with the normal rats consuming 1,25-dihydroxyvitamin D3 supplement. Urinary Ca excretionand Ca retention in panhisterectomized rats were not significantly different those of normal rats. WhileCa consumption and fecal Ca excretion were significantly reduced (P<0.05) in normal rats consuming 1,25-dihydroxyvitamin D3 supplement but urinary Ca excretion and Ca retention in normal rats consuming1,25-dihydroxyvitamin D3 supplement were not significantly different compare with normal rats notconsuming 1,25-dihydroxyvitamin D3 supplement. It is evident that panhisterectomy and 1,25-dihydroxyvitamin D3 supplement did not affect the calcium retention.